2007
DOI: 10.1073/pnas.0706251104
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of energetic changes accompanying urea-induced protein denaturation

Abstract: Because of its protein-denaturing ability, urea has played a pivotal role in the experimental and conceptual understanding of protein folding and unfolding. The measure of urea's ability to force a protein to unfold is given by the m value, an experimental quantity giving the free energy change for unfolding per molar urea. With the aid of Tanford's transfer model [Tanford C (1964) J Am Chem Soc 86:2050 -2059], we use newly obtained group transfer free energies (GTFEs) of protein side-chain and backbone units … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

29
406
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 266 publications
(437 citation statements)
references
References 37 publications
29
406
2
Order By: Relevance
“…We assigned the urea dependence entirely to the intrinsic, rather than interfacial, folding energies. This partitioning is consistent with a recent study indicating that the magnitude of m-value changes are dominated by peptide backbone exposure, 47 since the majority of the Notch ankyrin domain backbone units are involved in hydrogen bonds within (not between) repeats.…”
Section: The Landscape-based Modelsupporting
confidence: 92%
“…We assigned the urea dependence entirely to the intrinsic, rather than interfacial, folding energies. This partitioning is consistent with a recent study indicating that the magnitude of m-value changes are dominated by peptide backbone exposure, 47 since the majority of the Notch ankyrin domain backbone units are involved in hydrogen bonds within (not between) repeats.…”
Section: The Landscape-based Modelsupporting
confidence: 92%
“…The exclusion energies of the polar protein stabilizing osmolytes from the hydrophobic HPC chain, however, are comparable to the energies that have been ascribed to exclusion from the peptide backbone (8,11,26). This indicates that the exclusion of these osmolytes from nonpolar peptide side chains should significantly contribute to the stabilization of native protein structure.…”
mentioning
confidence: 78%
“…This, however, does not explain the chemical specificity of the interaction. Bolen and coworkers, for example, have concluded (8,11,12) that the inclusion of urea and the exclusion of stabilizing osmolytes from proteins are dominated by the interaction of these small molecules with the peptide backbone with little contribution from the exclusion of these polar solutes from hydrophobic side chains. One method for elucidating the physics of the interaction is to measure the distance dependence of the force through either a radial distribution function of solutes †…”
Section: Introductionmentioning
confidence: 99%
“…Recent work corrected the previous measurements for the activities of the model compounds in solution and showed that the strength of the hydrophobic interactions do not change substantially on transfer to urea, and that urea's favorable interaction with the protein backbone is responsible for its denaturing ability. 18 Thus, the free energy dependence of protein stability as a function of osmolyte concentration can be predicted if one assumes that the transfer free energies of solvent exposed sidechain and backbone groups on the native and denatured states are additive. [18][19][20] Here, using computational methods, we assess the transfer free energies of the peptide backbone from water to two osmolyte solutions, 2M urea and 2M TMAO.…”
Section: Introductionmentioning
confidence: 99%
“…18 Thus, the free energy dependence of protein stability as a function of osmolyte concentration can be predicted if one assumes that the transfer free energies of solvent exposed sidechain and backbone groups on the native and denatured states are additive. [18][19][20] Here, using computational methods, we assess the transfer free energies of the peptide backbone from water to two osmolyte solutions, 2M urea and 2M TMAO. The goal is to evaluate the peptide backbone transfer free energies as a function of chain length of oligoglycine peptides with capped end groups, and determine the extent to which the transfer free energies change in an additive manner with respect to chain length.…”
Section: Introductionmentioning
confidence: 99%